Factors that influencing the member’s intention to continue using the i-Akaun (EPF) / Siti Nur Nazmin Abdul Rahim - Abdul Rahim, Siti Nur Nazmin (Faculty of Business and Management, 2018)
The present research was conducted at Employees’ Provident Fund (EPF) Alor Gajah. This research and study was conducted to know the factors that influencing the member’s intention to continue using the i-Akaun in Alor Gajah. EPF i-Akaun allows the members to check their statements and to carry out certain withdrawals such as education and housing loan. However, the problem faced by the organization is that many members that already registered for the i-Akaun but do not use it. Therefore, this research will discover factors or reasons for members for not using it. Then, based on the factors determined, this study will identify which factors really influence the member’s intention to continue using the system. Lastly, to find the alternatives or ways to encourage the members to continue using the i-Akaun. The data were taken from 160 respondents using convenience sampling and the results results were analyzed and interpretations of relationships were made. The findings shows that only three has significant relationship with the dependent variable, which are trust, usability and quality of i-Akaun.